Wacława Juszkiewicz-Kamieńska in the service of another man - Gierczak, Grażyna (Nursing in the 21st Century, 2019)
WACŁAWA JUSZKIEWICZ-KAMIEŃSKA IN THE SERVICE OF ANOTHER MAN Introduction. Wacława Juszkiewicz-Kamieńska throughout her life served the sick, wounded and those in need of help. With great dedication, she became involved in social work for the nursing and veteran community. Aim. Presentation of a personal model of nurse, liaison officer and social activist. Material and methods. The work uses a biographical method. The technique of document and intelligence analysis was applied. Results. Wacława Juszkiewicz-Kamieńska became the model of a nurse who developed her own personality by serving the other person. From the first days of the war, as a nurse, she actively participated in the care of wounded soldiers and partisans, the sick and those in need of help. She served unselfishly in conspiratory outpatient clinics, sanitary points of the Polish Red Cross and in the Holy Trinity Hospital in Piotrków Trybunalski. In the post-war period, for eleven years, she conducted a vaccination campaign against tuberculosis, which at that time was a huge social problem. She became involved in training nurses and students. She was a co-creator of the Polish Nursing Association. Conclusions. Wacława Juszkiewicz-Kamieńska became the model of a nurse worthy of imitating and devoted to the development of nursing in the Piotrkowska Land. She deserves to remain in our memory forever.